2013
DOI: 10.1038/leu.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

The EUTOS prognostic score: review and validation in 1288 patients with CML treated frontline with imatinib

Abstract: The introduction of tyrosine kinase inhibitors (TKI) in the treatment of Philadelphia chromosome-positive (Ph+) chronic myeloid leukemia (CML) has revolutionized the outcome, but the prognosis of the disease is still based on prognostic systems that were developed in the era of conventional chemotherapy and interferon (IFN)-alfa. A new prognostic score including only two variables, spleen size and basophils, was developed for the prediction of complete cytogenetic response (CCyR) and progression-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 53 publications
(87 reference statements)
3
40
0
1
Order By: Relevance
“…[11][12][13] Average age of the population was 37.93 years. Mean spleen size was 10.2 cm which was grossly larger than what has been observed by Hoffman et al [14] This can be attributed to the lack of awareness in India about the disease amongst the patients and the basic healthcare personnel. Hence patients present usually in the late chronic phase.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[11][12][13] Average age of the population was 37.93 years. Mean spleen size was 10.2 cm which was grossly larger than what has been observed by Hoffman et al [14] This can be attributed to the lack of awareness in India about the disease amongst the patients and the basic healthcare personnel. Hence patients present usually in the late chronic phase.…”
Section: Discussionmentioning
confidence: 52%
“…Pagnano et al [16] have demonstrated a high CCyR of 83 % in similar subset of patients. But the difference among high and low risk group in achieving CCyR was statistically significant like that of Hoffman et al [14]. However, among Sokal risk group, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 54%
“…Complete cytogenetic remission (0 % Ph + marrow cell metaphases; CCyR) after 18 months of therapy was chosen as the primary outcome. The abilities of the EUTOS score to discriminate two risk groups with significantly different CCyR probabilities at 18 months and with significantly different progression-free survival probabilities over time were confirmed by an independent validation based on 616 and 1,190 patients, respectively [12].…”
Section: Eutos Scorementioning
confidence: 93%
“…In 2011, a simpler and TKI-specific score, the European Treatment and Outcome Study (EUTOS), was proposed but requires further confirmation before it can be widely used. 66 More recently, the response to TKIs at a given time point, disease risk and stage, BCR-ABL1 genotype, the presence of comorbidities, financial aspects and local monitoring capabilities are all being increasingly used to personalize treatment. 67 …”
Section: Prognostic and Predictive Factorsmentioning
confidence: 99%